Effects of a nurse-led eHealth cardiac rehabilitation programme on health outcomes of patients with coronary heart disease: A randomised controlled trial. (October 2021) - Su, Jing Jing; Yu, Doris Sau-fung
Abstarct: Background: The uptake of and adherence to cardiac rehabilitation remain suboptimal despite its apparent health benefits in modifying risk factors and slowing disease progression. eHealth refers to the use of information and communication technologies for health-related purposes. It is a promising approach for improving participation in cardiac rehabilitation by enabling instant contact, hypermedia information delivery, technology-monitored functionalities and individualised progress monitoring. Aims: To evaluate the effects of a nurse-led eHealth cardiac rehabilitation (NeCR) system on health behaviours, cardiac self-efficacy, anxiety and depression, health-related quality of life, risk parameters and unplanned use of care services for people with coronary heart disease. Design: A single-blinded randomised controlled trial design was used. Methods: The study randomly assigned 146 patients hospitalised for coronary heart disease to receive either the NeCR intervention or the usual care. Underpinned by social cognitive theory, the intervention commenced before hospital discharge with an in-person session by the nurse to identify individualised self-care needs, set goals and develop an action plan to enhance behavioural risk factor modification and orientate the patient to the use of the information and communication technology platform for cardiac rehabilitation. After discharge, the e-platform helped patients gain knowledge of disease management and monitor goal attainment for health behavioural changes. The nurse provided feedback on the patients' goal attainment and lifestyle modifications on a weekly basis in a small group format through the WeChat platform, thus also mobilising peer influence. Data for lifestyle behaviours, physiological risk parameters and clinical outcomes were collected at baseline and at 6 and 12 weeks post-intervention. Results: At 6 weeks post-intervention, participants in the intervention group showed significant improvement in the number of steps/day (β = 2628.48, p  = .022), the number of minutes/week sitting (β = −640.30, p  = .006) and their health-promoting lifestyle profile (β = 25.17, p  < .001) compared with the control group. Improvements in the number of steps/day (β = 2520.00, p  = .006), the number of minutes/week sitting (β = −719.73, p  = .004) and health-promoting lifestyle (β = 16.09, p  < .001) were sustained until the 12-week post-intervention endpoint. Moreover, participants showed significantly greater improvement in self-efficacy (β = 0.61, p  = .005) and health-related quality of life (mean difference = 0.56, p  < .001) than the control group at the study endpoint. Conclusions: The findings of this study demonstrate the effectiveness of the NeCR intervention in modifying behavioural risk factors and improving health-related quality of life. These findings also provide insights into the application of eHealth nursing interventions to enhance the rehabilitation of patients with coronary heart disease. Trial registration: ChiCTR1800020411